Improved outcomes during infrastructure closure with optimised asset management - Hermann, C.; Cannizzo, D. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Early planning for the closure of a mine can deliver improved financial outcomes for the closure project. Once the decision has been made to cease operations, the removal of the infrastructure is a cost that is typically not offset by a project-generated income. However, the costs associated with these assets can be optimised through modified management practices in late asset life. Planning for the disposal of mine site infrastructure typically focuses on a cost provision for decommissioning and demolition but excludes potential efficiencies that can be gained by improved asset management. Through early involvement of asset management and rundown-to-closure planning, it is possible to offset the infrastructure closure and removal costs by implementing more targeted and efficient management activities. The International Council on Mining and Metals (ICMM) Integrated Mine Closure Good Practice Guide (ICMM 2019) is widely recognised in the industry as a valuable supporting document for integrated closure planning. Further to this, there are established asset management standards and best practice guides, such as the ISO5500X suite of standards and The Asset Management Landscape published by the Global Forum On Maintenance & Asset Management. These resources exist to articulate and facilitate the coordinated activities of an organisation to realise value from assets. By aligning these guidance documents, we can incorporate broader asset management considerations into the infrastructure closure planning, with the objective of minimising the cost of closure by managing the assets more efficiently during the late operational life and the rundown-to-closure. Some examples of the broader asset management topics include spare parts and logistics, maintenance strategy, levels of service, identification of valuable and saleable assets, reliability of critical infrastructure, supply chain management, life cycle costing, asset information strategy and risk management. This paper discusses the importance of bringing forward infrastructure closure planning, by using the principals of integrated mine closure planning in conjunction with practice guidelines from asset management. Through informed planning and decision-making, it is possible to optimise the balance of cost, risk and performance for the management of the assets identified for closure.